Preliminary Kandungan Glibenclamide dan Metabolitnya 4-trans-hidroksiglibenklamid menggunakan Metode spektrofotometri Uv-Vis - Apriani, Aida; Muna, Tajul; Azhari, Saiful a (Journal of Pharmaceutical and Sciences, 2024)
Glibenclamide, another name for glyburide, is one of the antidiabetic drugs oral (ADO) which works by closing the K+-ATP channels in pancreatic beta cells thereby increasing insulin release. 4-trans-hydroxyglibenclamide is the main metabolite of glibenclamide which also has hypoglycemic effects. This study aims to determine the maximum wavelength of glibenclamide and its metabolite 4-trans-hydroxyglibenclamide. The results showed that the maximum wavelength of glibenclamide was at 300.60 nm, while 4-trans-hydroxyglibenclamide was at 299.50 nm and the glibenclamide calibration curve was obtained using the regression equation Y= Y=0.010x+0.001 with a correlation coefficient of 0.998, while 4 -trans-hydroxyglibenclamide Y= 0.0102x-0.0098 with a correlation coefficient of 0.99